Methicillin resistance in Staphylococcus aureus and coagulase-negative staphylococci: Epidemiological and molecular aspects - Martins, André [UNESP]; Cunha, Maria de Lourdes R. S. [UNESP] (Center Academic Publ Japan, 2007)
Infections caused by the genus Staphylococcus are of great importance for human health. Staphylococcus species are divided into coagulase-positive staphylococci, represented by S. aureus, a pathogen that can cause infections of the skin and other organs in immunocompetent patients, and coagulase-negative staphylococci (CNS) which comprise different species normally involved in infectious processes in immunocompromised patients or patients using catheters. Oxacillin has been one of the main drugs used for the treatment of staphylococcal infections; however, a large number of S. aureus and CNS isolates of nosocomial origin are resistant to this drug. Methicillin resistance is encoded by the mecA gene which is inserted in the SCCmec cassette. This cassette is a mobile genetic element consisting of five different types and several subtypes. Oxacillin-resistant strains are detected by phenotypic and genotypic methods. Epidemiologically, methicillin-resistant S. aureus strains can be divided into five large pandemic clones, called Brazilian, Hungarian, Iberian, New York/Japan and Pediatric. The objective of the present review was to discuss aspects of resistance, epidemiology, genetics and detection of oxacillin resistance in Staphylococcus spp., since these microorganisms are increasingly more frequent in Brazil.
Keywords: Coagulase-negative staphylococci; MecA; Oxacillin; Staphylococcus aureus; Aminoglycoside antibiotic agent; Beta lactam antibiotic; Chloramphenicol; Cotrimoxazole; Dalfopristin plus quinupristin; Erythromycin; Gentamicin; Linezolid; Macrolide; Meticillin; Minocycline; Oxacillin; Penicillin binding protein 2a; Penicillin G; Quinoline derived antiinfective agent; Rifampicin; Streptomycin; Tetracycline; Vancomycin; Bacterial gene; Bacterial genetics; Coagulase negative Staphylococcus; Coagulase positive Staphylococcus; Gene cassette; Gene insertion; Gene targeting; Genotype; Human; Immunocompetence; Immunocompromised patient; Mec1 gene; Mecr1 gene; Methicillin resistant Staphylococcus aureus; Molecular cloning; Molecular epidemiology; Nonhuman; Penicillin resistance; Phenotype; Regulator gene; Review; SCCmec gene; Staphylococcus infection; Anti-Bacterial Agents; Brazil; Coagulase; Disease Outbreaks; Humans; Methicillin; Methicillin Resistance; Phenotype; Staphylococcal Infections; Staphylococcus; Vancomycin